Research of Scale Inhibitors in Downhole Equipment - Pogrebnaya, Irina Alekseevna; Mikhailova, Svetlana Viktorovna (Civil Engineering Journal, 2019)
The article is devoted to the problem of salt deposition in the West-Agan field of Western Siberia in various types of oil equipment during the extraction and transportation of petroleum products, as well as research and identification of the most effective inhibitors. The article is devoted to the problem of salt deposits in various types of oil equipment during the extraction and transportation of petroleum products. Salinity (scale) adversely affects the surface of pipes, the working parts of pumps, installations in contact with formation waters. When this occurs, the parts are jammed or break. The article describes methods for solving the problem of scaling using inhibitors. The possibility of SIs supplying in the reservoir with the aim of its subsequent removal in the composition of the reservoir fluid [1-4]. The data on the adsorption-desorption capacity of scale inhibitors on core samples were studied. Adsorption was tested under dynamic conditions on the FDS-210 filtration unit, filled with a core from the West Agan field. The core was saturated with a scale inhibitor through pumping a 1% solution through it. Desorption of inhibitors was modeled by passing the bottom-water model through the cell under the same pumping conditions. The results of processing the experimental data are obtained; the figures are shown in the form of the dependence of the Freundlich equation relating the magnitude of adsorption to the current concentration of inhibitors, as well as the profile of the removal of Descum-2 scale inhibitors H-3611-Descum-4 and OEDPK. The paper presents the results of modeling the removal of Descum-2 inhibitors of the mark H-3611-A, Descum-4 of the mark S and OEDFC in the form of a table. The use of the studied inhibitors on the West Agan field allows to increase the duration of the maintenance-free period of the well equipment.